2007
DOI: 10.1080/10810730701672173
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Shame and Attitudes Toward Discussing the Results of Literacy Screening

Abstract: We investigated patients' willingness to have their reading ability documented in their medical records and the degree of shame and embarrassment associated with such disclosure. Structured interviews were conducted among a consecutive sample of 283 primary care patients at an urban public hospital. Patients' literacy was measured using the Rapid Estimate of Adult Literacy in Medicine (REALM). Self-report of degree of shame and embarrassment related to literacy skills was measured using an orally administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 27 publications
6
118
1
3
Order By: Relevance
“…Previous studies found similar acceptability. 33,34 The NVS was administered, on average, in less than 3 minutes, which demonstrates the utility of the NVS in primary care and which is consistent with prior findings. 35 The NVS would not be administered during every patient visit, but our data suggest that periodic reassessment should prove helpful to target patient-provider communication appropriately.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies found similar acceptability. 33,34 The NVS was administered, on average, in less than 3 minutes, which demonstrates the utility of the NVS in primary care and which is consistent with prior findings. 35 The NVS would not be administered during every patient visit, but our data suggest that periodic reassessment should prove helpful to target patient-provider communication appropriately.…”
Section: Discussionsupporting
confidence: 75%
“…Another limitation is selection bias within the included studies; we expect that low literacy patients, particularly those with fewer resources, may have declined study participation for fear of embarrassment or shame, a concern reported by other studies. 18,43 Had these patients participated, studies may have yielded different results. Further, in following the 2011 AHRQ protocol for relevant outcomes, we did not include studies examining the relationship of health literacy and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…They also have the advantage of being shorter and potentially less embarrassing for patients. 8,18,19 They therefore could allow for more efficient research about health literacy, as well as fewer negative feelings for patients involved in health literacy research. However, it is currently not clear whether self-reported measures have the same relationship to outcomes as the performance-based measures.…”
Section: Introductionmentioning
confidence: 99%
“…17 Second, specifically testing HL may cause patients to feel shame and/or embarrassment. 18,19 For these reasons, brief, onesentence items have been developed and tested to quickly identify in a non-threatening manner patients who are potentially at risk of having limited general HL and numeracy skills. 20 -25 This article was externally peer reviewed.…”
mentioning
confidence: 99%